2005
DOI: 10.1089/neu.2005.22.529
|View full text |Cite
|
Sign up to set email alerts
|

Functional Consequences of Lumbar Spinal Cord Contusion Injuries in the Adult Rat

Abstract: Our understanding of the substrates of locomotion, and hence our understanding of the causes of deficits following spinal cord injury, is still incomplete. While severe locomotor deficits can be induced by either contusion or laceration injuries or demyelination of thoracic spinal cord ventral and ventrolateral white matter, loss of mid-thoracic gray matter (intraspinal kainic acid injection) has no impact on locomotion. In contrast, loss of gray matter from the rostral lumbar segments induces severe locomotor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
113
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(118 citation statements)
references
References 35 publications
5
113
0
Order By: Relevance
“…Additionally, the chABC injection site may have played a role. Rat locomotion recovers to lesser extents following excitotoxic and contusion SCI at the rostral lumbar spinal cord [127][128][129]. Wheel running alone also did not improve locomotion recovery; however, task-specific and general rehabilitation alone each had positive, negative, or no effects on forelimb functional recovery [57].…”
Section: Pharmacological and Gene-delivery Approachesmentioning
confidence: 99%
“…Additionally, the chABC injection site may have played a role. Rat locomotion recovers to lesser extents following excitotoxic and contusion SCI at the rostral lumbar spinal cord [127][128][129]. Wheel running alone also did not improve locomotion recovery; however, task-specific and general rehabilitation alone each had positive, negative, or no effects on forelimb functional recovery [57].…”
Section: Pharmacological and Gene-delivery Approachesmentioning
confidence: 99%
“…17 If the injury was made one vertebral level caudal at the T12-T13 level, the injury would represent a caudal lumbar SCI, with animals recovering almost full function of the hindlimbs. 6 Therefore, significant efforts were taken to ensure a consistent and accurate landmarking procedure.…”
Section: Modeling Human Lumbar Scimentioning
confidence: 99%
“…3,4 Only a small number of models have been described for this location, however. [5][6][7][8][9][10] Injuries to the thoracolumbar region of the spine differ from injuries to the midthoracic or cervical regions because each results in distinct motor and sensory deficits. 3,4 It has been shown that interneurons involved in the hindlimb central pattern generator (CPG) are predominantly localized in the L1 and L2 spinal cord segments of the rat, 11 with injuries to this region resulting in significant locomotor deficits.…”
mentioning
confidence: 99%
See 2 more Smart Citations